Melamine Acetate Preparation as a Urea-Formaldehyde Resin Additive for Particleboard Production - Dicky Dermawan; Lukman Al Ghani; Aditya Bayu Prawidya (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Urea-formaldehyde (UF) resin binders for wood-based panel production often use melamine as an additive to improve both mechanical properties and environmental compliance. Direct fortification for efficient use of melamine remains a problem due to low solubility. Pizzi & coworkers suggested the use of more soluble melamine salts and demonstrated success in terms of product performance. However, their preparation method showed low productivity and inefficient use of material and energy. In their scheme, a batch reactor fed with 1 kg of water and 75 g of a stoichiometric amount of melamine and acetic acid produced only around 25 g of solid melamine acetate crystal. In contrast, the remaining 50 g remained dissolved in 991 g of water, which requires high of energy to evaporate. This paper reports an attempt to increase batch productivity and work towards the more efficient use of material and energy. The experiment showed that the successive addition of melamine and acetic acid to the batch up to the solubility limit of melamine at the same reaction condition increased melamine and acetic acid fed from 75 g to 165 g. This was followed by a significant increase in dry crystal yield from 25 g to 117 - 132 g. Feeding the mother liquor to the next batch decreased the water use to only 8% of the original requirement. This resulted in a highly efficient process, eliminating the need for energy-intensive melamine acetate recovery from the mother liquor. The addition of 2% - 4% wt. of the product to UF resin resulted in particleboard with significantly lower thickness swelling, an increase in MOR & IB strength, and lower formaldehyde emission.